Innovación en el cultivo del maní en Bolivia: Efectos de la interacción social y de las capacidades de absorción de los pequeños productores - Hartwich, Frank; Arispe, Tito; Monge, Mario (International Food Policy Research Institute, 2007)
This report presents the results of a study on local innovation in four peanut-producing regions in Bolivia. It aimed at identifying the type of organizations and mechanisms contributing the most to the adoption of innovations. The theoretical framework utilized suggests that farmers introduce and apply innovations as a combined result of their perceptions on the utility derived from doing so, and their individual and collective capabilities to absorb those innovations... [The] results guide to the conclusion that to achieve a larger and better participation of small peanut farmers in innovation processes, it is necessary to (1) adapt innovation sets to farmers absorptive capabilities; (2) try to improve the individual absorptive capabilities through financing schemes, training and sensibilization efforts; (3) promote and substantially intensify interactions among innovation providers and farmers, in a way that collective absorptive capabilities and a common learning on technology's applications and applicability can be developed; and (4) include other actors from the transportation, processing and exportation sectors in partnership arrangements, in order to improve their common understanding of production, quality and market opportunities, as well as to open and widen access to markets and to complementary financial support.